Impact of IVF on the Timing and Symptoms of Menopause - Muharam R; Sumapraja K; Pratama G; Azyati M; Prabowo KA (Dove Medical Press, 2021)
R Muharam, Kanadi Sumapraja, Gita Pratama, Mazaya Azyati, Kevin Ardito Prabowo Department of Obstetrics & Gynecology, Faculty of Medicine, University of Indonesia, Cipto Mangunkusumo National Hospital, Jakarta, IndonesiaCorrespondence: R MuharamDepartment of Obstetrics & Gynecology, Faculty of Medicine, University of Indonesia, Cipto Mangunkusumo National Hospital, Jl. Pangeran Diponegoro No. 71, Kenari, Kec. Senen, Kota Jakarta Pusat, Daerah Khusus Ibukota Jakarta, Jakarta, 10430, IndonesiaTel +62 812 85143491‬‬&#x202CEmail rmuharam@yahoo.comBackground: Age-related loss of female fertility is characterized by a decline in both the quantity and quality of ovarian follicles. Symptoms of ovarian stimulation, which is part of the process of in vitro fertilization (IVF), vary among women. This study was conducted to analyze the differences in menopausal timing and symptoms in women who had undergone IVF compared to those who had natural pregnancies.Methodology: In this cross-sectional study, menopausal women were categorized into two groups: those who had undergone IVF (n = 50) and those who had not (n = 50). Clinical data were obtained from the participants' medical records, and patient interviews were conducted using the menopause rating scale (MRS) questionnaires.Results: The IVF had no significant impact on psychological or somatic symptoms in either group (p> 0.05). However, it affected urogenital symptoms (p< 0.05). Additionally, there was a significant difference in the age of onset of menopause between the groups (p< 0.05).Conclusion: There is a significant correlation between IVF treatment, urogenital symptoms in menopause, and the age of onset of menopause.Keywords: in vitro fertilization, menopause, infertility, psychological symptoms, urogenital